Expression of the murine alpha B-crystallin gene in lens and skeletal muscle: identification of a muscle-preferred enhancer. - Dubin, R A (1991)
The alpha B-crystallin gene is expressed at high levels in lens and at lower levels in some other tissues, notably skeletal and cardiac muscle, kidney, lung, and brain. A promoter fragment of the murine alpha B-crystallin gene extending from positions -661 to +44 and linked to the bacterial chloramphenicol acetyltransferase (CAT) gene showed preferential expression in lens and skeletal muscle in transgenic mice. Transfection experiments revealed that a region between positions -426 and -257 is absolutely required for expression in C2C12 and G8 myotubes, while sequences downstream from position -115 appear to be determinants for lens expression. In association with a heterologous promoter, a -427 to -259 fragment functions as a strong enhancer in C2C12 myotubes and less efficiently in myoblasts and lens. Gel shift and methylation interference studies demonstrated that nuclear proteins from C2C12 myoblasts and myotubes specifically bind to the enhancer.